Analysis of E-commerce Talent Training Mode in Higher Vocational Colleges Based on Computer Big Data in Economic Management Practice Teaching. Issue 3 (October 2020) - Xu, Yuan
Abstract: In recent years, the development trend of e-commerce industry is good, and the market demand for e-commerce talents shows a rapid growth trend. According to the survey conducted by research, a famous analysis institution in China, the demand for e-commerce talents will reach more than 3 million. At present, based on computer big data, the talents trained by E-commerce Specialty in higher vocational colleges are far from meeting the market demand. However, from the employment situation in recent years, the employment rate of e-commerce graduates is lower than the national average employment rate. The reason lies in that the cultivation of practical ability of e-commerce graduates in most higher vocational colleges is far from the requirements of the market, enterprises and industries. Therefore, how to strengthen the cooperation between schools and enterprises, build a platform for practical teaching, and effectively improve the students' ability of practical innovation and entrepreneurship is an important subject of practical teaching reform of e-commerce specialty.